An unusual morphology and crystallization behavior in in situ formed polyphenylene oxide/polyamide 6 blends - Li, Yulin (2010)
Novel polyphenylene oxide/polyamide 6 (PPO/ PA6) blends were synthesized via in situ polymerization of e-caprolactam with PPO dissolved in it. The introduction of 10 wt% PPO into PPO/PA6 led to phase inversion of the blends, which was nearly completed by incorporating 15 wt% PPO into the blends. A single crystallization temperature (Tc) of PA6 was detected for PPO/PA6 with 1–4 wt% PPO, while double Tc existed in the blends with 6–15 wt% PPO. After eliminating previous thermal his tory, PPO/PA6 containing no more than 6 wt% PPO gave a single melting point (Tm), but the blends with 10–15 wt% PPO exhibited double Tm. Increasing PPO content in PA6 resulted in the transformation of its crystal form from a-crystal to c-crystal, which might be attributed to hin drance of crystallization of PA6 particles in PPO-rich phase.